Investment-Cash Flow Sensitivity and Growth Opportunities - EL Gaied, Moez (International Journal of Economics and Financial Issues, 2018)
The objective of this research is to examine the investment-cash flow sensitivity on a sample of 150 US firms during the period 1995-2012. This sensitivity can be attributed either to the problem of managerial discretion (Jensen (1986) and Jensen and Meckling (1976)) or to the problem of information asymmetry (Myers and Majluf (1984)). We used Tobin’s Q to split our sample as appropriate. Tobin’s low Q firms are thought to have a problem of managerial discretion, and Tobin’s strong Q schemes are supposed to display a problem of informational asymmetry. Our empirical results, which are in the same vein as that reported by Degryse and De Jong (2006), reveal that the sensitivity of investment to cash flows is greater for Tobin’s low-Q firms than for strong ones Tobin’s Q. Overall, our results are in line with the predictions of the hypothesis of managerial discretion. Keywords: Cash Flow, Investment Opportunities, Managerial Discretion, Information Asymmetry JEL Classifications: G11, G30, G32